Islam and Local Culture: A Comparative Study of Kerobok Mawlid in Kutai Kartanegara and Baayun Mawlid in Tapin - Duraesa, Muhammad Abzar; Syahrial, Syahrial; Dinihari, Anggie Nadia (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This study aims to explore the relationship between Islam and local culture, particularly the Baayun Maulid tradition in Banua Halat Village, Tapin Utara District, Tapin Rantau Regency and the Kerobok Maulid Kutai tradition in Tenggarong, Kutai Kartanegara Regency. It is qualitative research that employs a phenomenological approach. Tenggarong Community and Banua Halat Village Community were the study participants. This study's findings show that (1) The Kerobok Mawlid tradition is carried out in the month of Mawlid, which is intended to commemorate the birthday of the Prophet Muhammad SAW by reciting the barzanji. The Kerobok Mawlid tradition is carried out as a traditional ceremony of the Kutai Kingdom, which is marked by the presence of the sultanate's soldiers, who carry stretchers containing various kinds of traditional cakes, dozens of baskets of sinto or potpourri, and Astagona, walking around the palace. Furthermore, the Baayun Maulid tradition in Tapin Rantau Regency is also carried out in the month of Maulid to commemorate the birthday of the Prophet Muhammad SAW. This tradition is combined with the Maayun Anak tradition, the Banjar community custom of swinging children. (2) The relationship between Islam and the culture of Kerobok Maulid and Baayun Maulid is part of the manifestation of the existence of Islam in a culture. The reading of Sholawat and the Maulid as a form of Islamic identity in the Kutai and Banjar communities combined with customs shows the relationship between Islam and culture, which are inherently one unit and have harmony within them.